Pengaruh Konsentrasi Perekat Molase Terhadap Kualitas Briket Sekam Padi - Moh Akbar Suryo Prasetyo (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
This study aims to determine the effect of molasses adhesive concentrations on the quality of rice husk briquettes then to formulate optimal composition projections to approach national quality standards. This study employed an experimental method with a descriptive analysis design, in which briquette fabrication data at laboratory. The material processing technique for rice husk charcoal used a 50 mesh sieve, while the adhesive variations used progressive concentrations. Data collection techniques were conducted through temperature measurements and duration observations. The results showed that the 5 wt molasses concentration aspect achieved a heating value of 4,645 cal/g categorized as